Antepartum hemorrhage at a tertiary care teaching hospital in Nepal - Shrestha, Sarada Duwal; Shrestha, Reena; Singh, Alka; Sharma, Praban; Pradhan, Anagha Malla; Lama, Sushma (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Antepartum hemorrhage (APH) is a serious obstetrical emergency and is a leading cause of maternal and perinatal morbidity and mortality. Incidence varies from 2-5% of all deliveries. The maternal and perinatal complications of APH are anemia, postpartum hemorrhage, shock, low birth weight, intrauterine fetal death and birth asphyxia. Methods: This descriptive study was conducted at Department of Obstetrics and Gynaecology of Patan Hospital, a tertiary care teaching hospital of Patan Academy of Health Sciences (PAHS), Lalitpur, Nepal. All patients who were admitted after 22 weeks of gestation with diagnosis of antepartum hemorrhage from April 2012 to April 2016 were included. Results: The incidence of APH was 0.23% in the present study. Out of 84 patients, 39.3% were in age group of 25-29 years, 63% were multigravidae, 63% had placenta previa, 92.3% lower segment caesarean section done in new onset APH and 53.1% done in previous admitted cases of APH, 23.8% developed hypovolemic shock, 14.3% needed blood transfusion, 9.5% had postpartum hemorrhage, 1.2% had caesarean hysterectomy, 54.8% had preterm delivery, 9.5% were admitted in neonatal intensive care unit and perinatal mortality was 10.7%. Conclusions: APH is a major cause of maternal and perinatal morbidity and mortality. In our study, the most common cause of APH was placenta previa. The commonest mode of delivery was caesarean section. The major maternal complication was hypovolemic shock with consequent high blood transfusion rate and fetal complication in prematurity.